Penerapan Haversine Formula Pada Penerimaan Peserta Didik Baru Jalur Zonasi - Winoto, Sakti; Fadlil, Abdul; Umar, Rusydi (STMIK Budi Darma, 2020)
The government through the Ministry of Education and Culture issued a regulation on the admission of new students as stipulated in the Minister of Education Regulation Number 51 of 2018 to apply the zoning system. The regulation emphasizes that schools are required to give priority to prospective students who are in the domicile of the closest radius to the location of the school. To facilitate relevant agencies and the public in getting the closest school information in a zone, it is necessary to create an information system that can present information related to the existence or location of the school. One of the systems designed to solve and work with spatially referenced data or geographic coordinates is the Geographic Information System (GIS). Geographical Information Systems have the ability to perform data processing and freeze certain operations by displaying maps and able to analyze data properly. Research carried out applies the haversine formula in the search for the location of the closest school. To build digital maps using Google Maps, and developed with mobile services. The Google Maps API presents the programming functions provided by Google Maps for integration in the web or the application that is being created. While information about school data is presented and integrated in the goegraphic application.